Shortterm outcomes of downreferral in provision of paediatric antiretroviral therapy at Red Cross War Memorial Children’s Hospital Cape Town South Africa: A retrospective cohort study - J Copelyn (South African Medical Journal, 2018)
Background. The large scale-up of paediatric HIV care necessitated down-referral of many children receiving antiretroviral therapy (ART) from Red Cross War Memorial Childrenâ€™s Hospital (RCWMCH), Cape Town, South Africa. Few published data exist on the outcomes of these children.Objectives. To assess outcomes of children receiving ART in the first 12 months after down-referral to primary healthcare (PHC) clinics and identify determinants of successful down-referral.Methods. A retrospective cohort study of children <15 years of age who initiated ART at RCWMCH and were subsequently down-referred to one of two PHC clinics between January 2006 and December 2012 was completed. Baseline characteristics of patients and caregivers as well as CD4+ counts, viral loads (VLs) and weights were collected 6 and 12 months after down-referral. Outcomes included retention in care and viral suppression.Results. Of 116 children down-referred to the two study PHC clinics, 81.9% arrived at the designated PHC clinic and a further 8.6% continued care at other clinics, the remaining 9.5% being lost to follow-up. Of those successfully down-referred, 11.4% took >8 weeks to present, possibly experiencing treatment interruption. At 12 months after down-referral, only 81.0% remained in care. No factors were associated with retention in care in multivariable analysis. For children who remained in care at the designated PHC clinics, the clinical and immunological gains achieved prior to down-referral were sustained through 12 months of follow-up, and 54.7% of this cohort had documented viral suppression at 12 months. However, if only children with VL results are considered, 75.9% (41/54) were virally suppressed 12 months after down-referral.Conclusions. Down-referral of children on ART is complex, with risk of loss to follow-up and treatment interruption.Â